Digital Scholarship as Handwork and Brainwork: An Early Modern History of Cryptography. - ELLISON, KATHERINE (Journal for Early Modern Cultural Studies, 2013)
The first computing machines, invented by Samuel Morland during the seventeenth century, were distributed as part of a rhetorical project underway at the time that was orchestrated by Royal Society members like Morland and John Wilkins. Products of both brainwork, or creative innovation, and handwork, or craft production, these machines reconnect early modern scholars with the historical meaning of "digitization" as the manipulation of media with the hand and challenge assumptions about the differences between humanities scholarship and computer science scholarship. Through their pocket-sized devices and, I examine, their cryptography manuals, they sought not only to reconceive the composition and reading processes as digital, or always involving the hand, but also to create a respected, collaborative place for the sciences and technical arts in both higher education and the public imagination. Both were particularly interested in cryptography and its multimodal, cross-disciplinary potential for the global sharing of knowledge for England's national intellectual and economic status and position that discipline as a liberal art. However, Wilkins's advocacy for richer disciplinary collaboration across the liberal arts, sciences, and technical arts set into motion a history of division that today's digital humanists must navigate in order to develop purposeful online early modern scholarship.